Extracorporeal shockwave lithotripsy versus ureteroscopic laser lithotripsy in proximal ureteric calculus of 10 to 20 mm in size: a single centre experience - Pushpanathan, Mugialan; Fahmy, Omar Ahmed; Siang, Christopher Lee Kheng; Khairul-Asri, Mohd Ghani (Pavlov University, 2023)
OBJECTIVE. To investigate the efficacy of extracorporeal shockwave lithotripsy (ESWL) and ureteroscopic laser lithotripsy (URS) treatment of upper ureteric stones between 10 to 20 mm in size. From January 2020 to January 2023, 75 patients were treated for proximal ureteric calculus between using ESWL (n=40) & URS (n=35). METHODS AND MATERIALS. Both groups were compared regarding operative time, success rate and complications who underwent treatment for proximal ureteric calculus of 10–20 mm in diameter. URS group was observed to have higher stone-free rate, compared to the ESWL group, 31 (88.6 %) vs 20 patients (50.0 %) (p<0.001). RESULTS. URS treatment had a higher complication rate compared to the ESWL, 9 (25.7 %) vs 3(7.5 %);(p=0.032). Procedure time for URS was longer, compared to the ESWL, median (IQR) for URS vs ESWL were 78.0 (65.0, 100.0) vs 62.0 (48.0, 67.0) minutes; (p<0.001). CONCLUSION. We conclude that URS has a better stone-free rate in comparison to a single session of ESWL for upper ureteral calculus of 10–20 mm, with higher complication rates such as post-operative fever and pain. © 2023 Pavlov University. All rights reserved.